2021
DOI: 10.1002/dad2.12248
|View full text |Cite
|
Sign up to set email alerts
|

Is diabetes associated with increased pathological burden in Alzheimer's disease?

Abstract: Introduction:We examined the association between Alzheimer's disease (AD) and type 2 diabetes mellitus (DM) and hypothesized that diabetes is associated with an increased pathological burden in clinically and pathologically diagnosed AD. Methods: All data were obtained from the Uniform Data Set (UDS) v3, the Neuropathology Data Set, and the Researcher's Data Dictionary-Genetic Data from the National Alzheimer's Coordinating Center. The dataset (37 cases with diabetes and 1158 cases without) relies on autopsy-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Thus, the cases of all-cause dementia among APOE ε4 noncarriers may include a greater number of vascular dementia, whereas APOE ε4 is associated with bona fide “pure” AD. Studies in which AD diagnosis is limited to neuropathologically confirmed cases have consistently found no association with type-2 diabetes or metabolic syndrome (Abner et al, 2016; Groeneveld et al, 2019; Hassing et al, 2002; Heyman et al, 1984; Peila et al, 2002; Sadrolashrafi et al, 2021; Thambisetty et al, 2013). Likewise, we find disparate effects of type-2 diabetes and AD on cerebral glucose transporters (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the cases of all-cause dementia among APOE ε4 noncarriers may include a greater number of vascular dementia, whereas APOE ε4 is associated with bona fide “pure” AD. Studies in which AD diagnosis is limited to neuropathologically confirmed cases have consistently found no association with type-2 diabetes or metabolic syndrome (Abner et al, 2016; Groeneveld et al, 2019; Hassing et al, 2002; Heyman et al, 1984; Peila et al, 2002; Sadrolashrafi et al, 2021; Thambisetty et al, 2013). Likewise, we find disparate effects of type-2 diabetes and AD on cerebral glucose transporters (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…RAGE activation regulates βand γ-secretase cleavage of amyloid precursor protein, to generate Aβ [67]. Membrane-bound RAGE has also been shown to transport Aβ into the brain [68] by mediating amyloid transport across the blood-brain barrier [69,70]. A mouse transgenic model of AD showed that Aβ binds to RAGE, resulting in transport of Aβ from the bloodstream across the blood-brain barrier [70].…”
Section: Ages In Neurocognitive and Mental Disorders: Mechanisms Of A...mentioning
confidence: 99%
“…95 However, others failed to show a correlation between type II diabetes and AD pathology. 96,97 Furthermore, in several diabetic mouse models of AD, increased tau phosphorylation is observed. 98 Indeed, defects in insulin receptor function, induced in rats by intracerebroventricular injection of streptozotocin, led to impaired learning, memory and cognition, along with decreased glucose uptake and oxidative glucose metabolism.…”
Section: Does a Loss Of Insulin Signalling Reduce Glucose Uptake In N...mentioning
confidence: 99%